Analisis Kinerja Kelompok Tani di Kecamatan Sungai Kakap - Kurniati, Dewi; Permatasari, Nia (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
In Sungai Kakap District, farmer groups serve as a platform for farmers to enhance production capacity, adopt agricultural technology, and strengthen collaboration among members. However, the performance of farmer groups in this area still faces several challenges, such as low member participation, lack of innovation, and limited access to resources. This study aims to analyze the performance of farmer groups in Sungai Kakap District. A quantitative descriptive approach was employed, with a purposive sampling technique selecting 50 farmer groups and 150 farmer group members across 13 villages. Data were analyzed using descriptive analysis and scoring techniques. The results indicate that the overall performance of farmer groups in Sungai Kakap District falls into the good category. Farmer groups have effectively fulfilled their three main functions: as a learning class, a collaboration platform, and a production unit. Improving the performance of farmer groups in Sungai Kakap District can be achieved through enhancing managerial capacity, strengthening internal capital, improving the quality of learning classes, reinforcing external partnerships, conducting regular evaluations and monitoring, and increasing member participation.